2007
DOI: 10.4184/asj.2007.1.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Abscess with Pyogenic Arthritis of Facet Joint Treated with Antibiotic-Bone Cement Beads - A Case Report -

Abstract: Most epidural abscesses are a secondary lesion of pyogenic spondylodiscitis. An epidural abscess associated with pyogenic arthritis of the facet joint is quite rare. To the best of our knowledge, there is no report of the use of antibiotic-cement beads in the surgical treatment of an epidural abscess. This paper reports a 63-year-old male who sustained a 1-week history of radiating pain to both lower extremities combined with lower back pain. MRI revealed space-occupying lesions, which were located in both sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, the appearance of a synovial cyst on CT is not typically associated with bone erosion but it may present with sclerosis, gas or calcifications in the cyst capsule [14]. In contrast to synovial cysts, bone erosion is reported frequently with PFJ [6, 15]. On T2-weighted MRI scans, PFJ demonstrates widening of the facet joint space as well as erosion and swelling (Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…However, the appearance of a synovial cyst on CT is not typically associated with bone erosion but it may present with sclerosis, gas or calcifications in the cyst capsule [14]. In contrast to synovial cysts, bone erosion is reported frequently with PFJ [6, 15]. On T2-weighted MRI scans, PFJ demonstrates widening of the facet joint space as well as erosion and swelling (Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have used antibiotic bone cement beads [21], a combination of antibiotic-impregnated BGS and autograft [22] or bioactive glass S53P4 [23]. In our opinion, the advantage of the injectable calcium sulfate/hydroxyapatite composite plus gentamicin is the high local concentration of gentamicin at the desired location [24], the complete resorption of the BGS, and its osteoconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dissemination of abscess in the facet joint of the vertebrae to the epidural space, Lee et al [ 10 ] reported that good outcome could be achieved using antibiotics cement beads. Our patient was treated by surgical debridement of the abscess followed by intravenous and oral antibiotics, and good outcome was obtained during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Most pyogenic arthritis of the facet joint is considered to be secondary to spinal osteomyelitis of the vertebral body. Nonetheless, in some cases bacterial invasion of the facet joint by hematogenous dissemination without associated vertebral body osteomyelitis have been reported [ 10 ]. Based on these experiences, direct bacterial invasion is thought to co-exist with secondary dissemination of osteomyelitis in the vertebral body.…”
Section: Discussionmentioning
confidence: 99%